Extracranial Meningioma in the Scalp with Concurrent Steatocystoma - Jiankun Tong; Sergei A. Aksenov; Mitchell I. Chorost; William H. Rodgers (Hindawi Limited, 2020)
This report documents a rare case of an extracranial meningioma on the posterior scalp without apparent dural connection. Additionally, a sebaceous steatocystoma of the anterior scalp presented alongside the meningioma. A steatocystoma localized to the scalp is also remarkably rare. To our knowledge, this is the first report documenting both an extracranial meningioma and a steatocystoma presenting concurrently on the scalp. A male patient in his thirties presented with a mass lesion on the scalp. A CT scan revealed one posterior scalp mass with no intracranial abnormalities. Post excision histologic examination confirmed an extracranial meningioma (meningothelial variant, WHO Grade I). A second anterior scalp mass, not revealed by CT scan, was discovered during surgery. It was excised and diagnosed as a steatocystoma. Meningiomas predominantly occur intracranially but, in some instances, may present as a standalone extracranial tumor without intracranial abnormalities. Because extracranial meningioma is uncommon, it may be overlooked during clinical diagnosis of scalp masses. We recommend that this neoplasm be routinely considered in the differential diagnosis of extracranial tumors. The discovery of another rare tumor-a steatocystoma located in immediate proximity on the scalp-is further remarkable. We briefly review relevant case reports and etiologies and consider a potential relationship between the two neoplasms. However, it remains more likely that the concurrence of these tumors in our patient was simply coincidental.